Analysis of Formulation of National Development Risk Management Policy Using Regulatory Impact Analysis Method - Butarbutar, Hilman; Umanto, Umanto (Journal of Governance, 2025)
The existence of several government program failures that occurred finally forced the government to issue Presidential Regulation Number 39 of 2023 concerning National Development Risk Management or “Manajemen Risiko Pembangunan Nasional” (MRPN). MRPN is aiming to manage cross-sectoral risks crucial to achieving Indonesia’s 2045 vision. However, the formulation of this policy needs to be analyzed so that its impact on the common good becomes clearer.  Regulatory Impact Analysis (RIA) is essential in shaping policies to mitigate overlapping regulations and enhance national development. The research uses a qualitative paradigm that combines document reviews and in-depth interviews with key informants who focus on their roles in policy drafting and risk management. The results, MRPN, are a significant step toward national development risk management, but improvements in policy alternatives, stakeholder engagement, and cost-benefit analyses are required for better outcomes. Enhancing inter-entity coordination to ensure technical guidelines are actionable policies and making a user-friendly technological tool to facilitate communication and data management among stakeholders is also essential to make policy implementation effective.